PENGARUH SIKAP, NORMA SUBJEKTIF, KONTROL PERILAKU, MOTIVASI SPIRITUAL TERHADAP MINAT MAHASISWA AKUNTANSI DALAM MEMILIH KONSENTRASI AKUNTANSI SYARIAH DI FAKULTAS EKONOMI UNIVERSITAS SYIAH KUALA - islamylia, islamylia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study aimed to examine the effect ofÂ  attitudes, subjective norms, behavioral control and intention spiritual motivation towards students majoring in accounting in selecting accounting concentration di faculty sharia economy. 2011 â 2013 population who have chosen and take sharia accounting faculty university syiahkuala randomly selected number 59. Collection of data and information needed in the study conducted by the research field. The data used are primary data obtained directly from the subject of research in the form of a questionnaire. Testing the influence of the independent variable on the dependent variable is done by using a multiple regression model by using SPSS software version 21.0.The results showed that either partially or simultaneously, the four variables subjective norms, behavioral control and spiritual motivational effect on students intention sharia accounting role in choosing a concertration in student service branch in 2011, 2012 and 2013.